Teachers’ Self-Efficacy in the Use of Information and Communication Technology for Teaching Basic Technology in Ilorin Metropolis - TIJANI, Abdullahi Ayomide; TOLORUNLEKE, Emmanuel Adebayo (Ilorin Journal of Education, 2023)
This study examined the teachers’ self-efficacy in the use of information and communication technology for teaching basic technology in Ilorin metropolis. The study was a descriptive type using the survey method. Researcher designed questionnaire was used to elicit the views from the respondents. Sample comprised 262 Basic Technology teachers in upper basic schools in Ilorin. Data were analysed using mean to answer research questions 1 and 4 and t-test was used to test research hypothesis 1. The findings of the study showed that; basic technology teachers always use the basic ICT tools for teaching with Grand Mean of 2.83, the self-efficacy level of basic technology teachers in the use of ICT is moderate in teaching basic technology with Grand Mean of 2.93, basic technology teachers are perceived to possess strong self-efficacy in the use of ICT with a grand mean of 2.71, ICT adds value to teaching of Basic Technology with a grand mean of 3.12, there was no significant difference between male and female Basic Technology teachers’ in their self-efficacy in the use of ICT with t (260) = 0.49, p > 0.05. The study concluded that basic technology teachers are skilled in the use of ICT for teaching. It was recommended among others that Government, NGOs and individuals should also make available facilities needed to access ICT, either by reducing the price or making it free of charge.